PENGARUH EDUKASI FIRST AID KEGAWATDARURATAN TERHADAP PENGETAHUAN PENANGANAN FRAKTUR PADA ORANG AWAM ATAU MASYARAKAT SEKITAR KAMPUS STIKES MUHAMMADIYAH MANADO - Siti Qomariah Andini Sari; Suwandi Luneto; Rahmat H. Djalil (Jurnal Rumpun Ilmu Kesehatan, 2022)
Emergency is defined as a condition that can threaten the safety of life if it is not treated immediately, and this can happen to anyone, anywhere and anytime. First aid is the immediate and temporary care given to a person. Health education with educational method is defined as a method that can increase the insight and knowledge. The objective of this study is to determine the effect of emergency First Aid education on fracture management knowledge in the community around STIKES Muhammadiyah Manado.The research design used was a quasi-experiment, with a one group posttest research design. In this study, the research sample selected was 12 research respondents, in the selection using random sampling. In collecting research data, this was conducted by distributing research questionnaires to the research respondents. Then, the research data that has been collected is processed using with the Mc-Nemar’s test, with a value level of a ≤ 0.05.The results of this study indicate that there is an effect of emergency first aid on fracture management knowledge with value of p = 0,004 where p value is smaller than a = 0.05. There is an effect of education on the effect of emergency First Aid education on knowledge of fracture management in lay people or the community around the STIKES Muhammadiyah Manado.